2006
DOI: 10.1037/0735-7028.37.1.83
|View full text |Cite
|
Sign up to set email alerts
|

The effects of full-day and half-day workshops for health care providers in techniques for increasing resistant clients' motivation.

Abstract: Are psychotherapy training workshops worth the time and money? The current study examined the effectiveness of 3-hr and 6-hr versions of a workshop for health care providers in techniques for increasing motivation in resistant clients. Role plays were used to examine pretraining and posttraining behavior of graduate student and clinician participants from various health care fields. Both workshops were associated with higher levels of workshop-consistent behavior and lower levels of workshopinconsistent behavi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
15
0

Year Published

2008
2008
2018
2018

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(16 citation statements)
references
References 47 publications
1
15
0
Order By: Relevance
“…Seven studies supplemented self-report with behavior observation measures; one study supplemented self-report with chart review. Interestingly, some of the studies that used behavior observation methods used simulated clients as part of their assessment strategy (Baer, Rosengren, Dunn, Wells, & Ogle, 2004; Baer et al, 2009; DeViva, 2006; Dimeff et al, 2009; Freeman & Morris, 1999;W. R. Miller & Mount, 2001b; W.…”
Section: Resultsmentioning
confidence: 99%
“…Seven studies supplemented self-report with behavior observation measures; one study supplemented self-report with chart review. Interestingly, some of the studies that used behavior observation methods used simulated clients as part of their assessment strategy (Baer, Rosengren, Dunn, Wells, & Ogle, 2004; Baer et al, 2009; DeViva, 2006; Dimeff et al, 2009; Freeman & Morris, 1999;W. R. Miller & Mount, 2001b; W.…”
Section: Resultsmentioning
confidence: 99%
“…It would be beneficial in future studies to follow up the clients directly, rather than relying on the clinician's judgment regarding client outcomes (Baer et al, 2004;McGovern et al, 2004;Miller et al, 2004;Miller et al, 2006;Morgenstern et al, 2001Sholomskas et al, 2005. While half-day didactic workshops are not best practice (Resnicow et al, 2002;Velasquez et al, 2000), these workshops are the most common and practical way of disseminating postgraduate training in real world settings (Baer et al, 2004;DeViva, 2006;Miller & Mount, 2001;Sholomskas et al, 2005). In future studies, in addition to examining clinician behaviour, outcomes of the clients would also need to be measured in a systematic and objective manner.…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, little is known regarding the translation of the manualised interventions in research settings to effective clinical interventions in everyday practice (Baer et al, 2004;McGovern, Fox, Haiyi, & Drake, 2004;Miller et al, 2004;Miller, Sorensen, Selzer, & Brigham, 2006;Morgenstern, Morgan, McCrady, Keller, & Carroll, 2001;Rubak, Sandboek, Lauritzen, Borch-Johnsen, & Christensen, 2006;Sholomskas et al, 2005). The most common form of disseminating evidence-based practice to health professionals is through a single (0.5-2 day) didactic workshop (Baer et al, 2004;DeViva, 2006;Miller & Mount, 2001;Sholomskas et al, 2005). Transferring evidence-based treatment into healthcare settings is most effective when the workshop (a) describes the principles underlying the intervention; (b) provides coaching and practice, such as role-playing (Miller & Mount, 2001 Miller et al, 2006;Resnicow, Dilorio, Soet, Borrelli, & Hecht, 2002;Schoener et al, 2006;Sholomskas et al, 2005); (c) involves follow-up supervision or feedback for the clinicians (Miller & Mount, 2001;Miller et al, 2004;Miller et al, 2006;Morgenstern et al, 2001;Resnicow et al, 2002;Schoener et al, 2006;Sholomskas et al, 2005) and (d) includes motivational interviewing (MI) and cognitivebehavioural techniques (CBT) (Baer et al, 2004, Miller et al, 2004, Miller et al, 2006.…”
mentioning
confidence: 99%
“…Miller et al (2004) reported that the standard client-actors in their role-plays tended to produce the same responses to therapists over time; the authors commented that this was not representative of how therapy clients respond to MI. Instructions to actors on the level of compliance with therapist directions have also varied: while Dimeff et al (2009) instructed actors to be reasonably compliant with DBT skills coaching, DeViva (2006) instructed actors to return to a resistant stance to provide more opportunities for the therapist to use MI. Finally, the degree to which actors are monitored during role-play assessment has differed across studies.…”
Section: Role-play Assessment Of Skillmentioning
confidence: 99%
“…Reactions to training have been examined by therapist self-report, often using a few items rated on a Likert-type scale (Baer et al 2009;DeViva 2006;Gega et al 2007;Jensen-Doss et al 2009;Morgenstern et al 2001;National Crime Victims Center 2007;Russell et al 2007;Worrall and Fruzzetti 2009). See Table 3 for a summary including timing of assessment, scaling, and results.…”
Section: Therapist Self-reportmentioning
confidence: 99%